1975
DOI: 10.1037/h0076381
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of orthogonal and nonorthogonal analysis of variance.

Abstract: Much of the controversy surrounding dummy variate multiple regression approaches to nonorthogonal analysis of variance would be cleared up if a criterion could be accepted for deciding what constitutes a proper generalization of the classical analysis of variance for orthogonal factorial designs. It is proposed that a general multiple regression solution be interpreted as testing analysis of variance effects only if it results in an estimation of the same parameters and tests of the same hypotheses that might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1

Year Published

1977
1977
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 16 publications
1
32
1
Order By: Relevance
“…As for reaction times, a two-way nonorthogonal ANOVA (Overall & Spiegel, 1969;Overall, Spiegel, & Cohen, 1975) indicated that the main effects of change amplitude, F(9, 558) ¼ 10.16, p , 0.01) and position, F(1, 558) ¼ 11.12, p , 0.01, are both significant, but interaction, F(9, 558) ¼ 0.83, ns, is not significant.…”
Section: Resultsmentioning
confidence: 88%
“…As for reaction times, a two-way nonorthogonal ANOVA (Overall & Spiegel, 1969;Overall, Spiegel, & Cohen, 1975) indicated that the main effects of change amplitude, F(9, 558) ¼ 10.16, p , 0.01) and position, F(1, 558) ¼ 11.12, p , 0.01, are both significant, but interaction, F(9, 558) ¼ 0.83, ns, is not significant.…”
Section: Resultsmentioning
confidence: 88%
“…Those results indicate that the significant sex difference in alcohol behavior disappears when differences due to occupation are partialed out. The method of analysis and interpretation were same as discussed by Overall, Spiegel, and Cohen (1975). Because interest here is in illustrating the potential of general linear model analysis of categorical data, no further discussion of the results obtained from analysis of the 4-point alcohol behavior scale will be undertaken at this time.…”
Section: Recent Investigations Bymentioning
confidence: 99%
“…In a nonorthogonal design, the least squares regression method provides estimates of the same response probabilities that are estimated from the marginal response frequencies in a balanced design involving the same factors. This is an extension of the argument used by Overall, Spiegel, and Cohen (1975) in proposing a criterion for equivalence of orthogonal and nonorthogonal designs for ANOVA with quantitative dependent variables.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…We use effects-coding of the factors in the matrices X and Z (Overall, Spiegel, and Cohen 1975). It is important to note that Equation 3 is the equation that is of key interest for inference.…”
Section: Banova Modelsmentioning
confidence: 99%